The unknown Battle of Midway : the destruction of the American torpedo squadrons - Kernan, Alvin B. (Yale library of military history., 2005)
The Battle of Midway is considered the greatest U.S. naval victory, but behind the lustre is the devastation of the American torpedo squadrons. Of the 51 planes sent to attack Japanese carriers only 7 returned, and of the 127 aircrew only 29 survived. Not a single torpedo hit its target. A story of avoidable mistakes and flawed planning, The Unknown Battle of Midway reveals the enormous failures that led to the destruction of four torpedo squadrons but were omitted from official naval reports: the planes that ran out of gas, the torpedoes that didn't work, the pilots who had never dropped torpedoes and the breakdown of the attack plan. Alvin Kernan, who was present at the battle, has written a troubling but persuasive analysis of these and other little-publicised aspects of this great battle. The standard navy tactics for carrier warfare are revealed in tragic contrast to the actual conduct of the battle and the after-action reports of the ships and squadrons involved.